2012
DOI: 10.1111/j.1477-9552.2012.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Production Risk and Technical Efficiency in Organic and Conventional Agriculture – The Case of Arable Farms in Germany

Abstract: This paper quantifies the importance of production risk and technical efficiency as two possible sources of production variability in German organic and conventional farming. Determinants of production risk and inefficiency are investigated based on a combination of Just and Pope’s stochastic production framework and a Stochastic Frontier Analysis. The empirical analysis is conducted using a balanced panel of farm records from 1999/2000 to 2006/2007 on 37 organic and conventional arable farms, respectively. Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 48 publications
8
36
0
1
Order By: Relevance
“…This is consistent with the findings in previous literature that better quality soils can supply better nutrient to crops and, hence, can achieve more stable rice production compared with poorer soils [24,29]. In contrast, weather events, like drought and flood, have a risk-increasing effect on output.…”
Section: Estimation Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the findings in previous literature that better quality soils can supply better nutrient to crops and, hence, can achieve more stable rice production compared with poorer soils [24,29]. In contrast, weather events, like drought and flood, have a risk-increasing effect on output.…”
Section: Estimation Results and Discussionsupporting
confidence: 82%
“…With a positive (negative) marginal production risk, a risk-averse farmer uses less (more) of the specific input than the risk-neutral farmer, and the input is known as risk-increasing (decreasing) by this output [24]. Kumbhakar [21] suggested a flexible approach to incorporate the inefficiency term with the Just and Pope function, by which the determinants of inefficiency are also examined:…”
Section: Integration Of Risk Into Stochastic Frontier Analysismentioning
confidence: 99%
“…For example, organic olive farms in Greece [8] and organic dairy farms in Germany [14] seem to use respectively less or similar labour than their conventional counterparts. Similar to the studies reported above, labour requirements on arable farms are in most cases higher on organic farms [20][21][22][23]31,32].…”
Section: Labour Use and Technical Efficiencysupporting
confidence: 75%
“…Three studies report lower labour use on organic dairy farms compared to conventional [14][15][16][17], and three suggest the opposite [1,18,19]. Likewise on organic arable cropping both cases of higher [18,20,21] and lower [20,22,23] labour use than conventional farms are reported.…”
Section: Labour Use and Farm Structurementioning
confidence: 99%
See 1 more Smart Citation